Sistem Pemungutan Suara Elektronik Menggunakan Model Poll Site E-Voting - Haryati, Haryati; Adi, Kusworo; Suryono, Suryono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
General elections is a regular agenda for a democtaric state, the applied paper based voting has several drawbacks, including spoiled ballots, inaccuracy in the counting of votes and reporting of election results which tends to be slow. Therefore , it needs to develop an electronic voting system that is user friendly for Indonesian people, which will reduce confusion from the previous system changes. Electronic voting aims at increasing participation, accuracy and efficiency of election results. Electrinoc voting has its own challenges to the implementation in Indonesia, ranging from the lack of legal protection, the heterogeneous level of education, culture, soceity and the digital gaps. The model developed in this thesis is the poll site e-voting, based on the rules of General Elections Commision (KPU) as the organizer of the elections. In this model, people still go to the pools, using the ID number od ID card as a verification tool and voting at the voting booths provided. The system automatically stores the results in a database option, and after the spesified time will show both the results of the voting and other and other information required by the Commission. Voting system with a model of e-voting poll site is expected to have a good chance an a low level of risk to be applied in Indonesia. Â  Keywords : E-voting; Poll site; Rule based; Risk.